Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/1932296819860133
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CGM-Derived Measures of Glycemic Variability Between Pancreatogenic Diabetes and Type 2 Diabetes Mellitus

Abstract: Background: To compare glycemic variability (GV) indices between patients with fibrocalculous pancreatic diabetes (FCPD) and type 2 diabetes mellitus (T2D) using continuous glucose monitoring (CGM). Methods: We measured GV indices using CGM (iPro™2 Professional CGM, Medtronic, USA) data in 61 patients each with FCPD and T2D who were matched for glycated hemoglobin A1c (HbA1c) and duration of diabetes. GlyCulator2 software was used to estimate the CGM-derived measures of GV (SD, mean amplitude of glycemic excur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 37 publications
(62 reference statements)
0
18
1
Order By: Relevance
“…To date, GV has mostly been investigated only as a risk factor for mortality in critically ill patients 21,22 . Further, high GV (assessed with the use of continuous glucose monitoring) has been shown to be significantly associated with the presence of diabetes in cross‐sectional studies in the setting of chronic pancreatitis 23,24 . However, changes in GV (and, by extension, possible usefulness of continuous glucose monitoring) in unselected AP patients is an unchartered territory.…”
Section: Discussionmentioning
confidence: 99%
“…To date, GV has mostly been investigated only as a risk factor for mortality in critically ill patients 21,22 . Further, high GV (assessed with the use of continuous glucose monitoring) has been shown to be significantly associated with the presence of diabetes in cross‐sectional studies in the setting of chronic pancreatitis 23,24 . However, changes in GV (and, by extension, possible usefulness of continuous glucose monitoring) in unselected AP patients is an unchartered territory.…”
Section: Discussionmentioning
confidence: 99%
“…The present study represents an important expansion of our prior work on CGM-derived measures of glycemic variability in patients with T2D and FCPD. 23 In this study, we used CGM to assess hypoglycemic events and hypoglycemia-associated indices in patients with diabetes of the exocrine pancreas. We found that the majority of patients experienced hypoglycemic events with significant alterations in hypoglycemic indices.…”
Section: Discussionmentioning
confidence: 99%
“…CGM was carried out using the iPro®2 (Medtronic, MiniMed Northridge, CA, USA), which was placed on each participant's abdomen before lunch on the day before the test. The following CGM variables were calculated: daily mean blood glucose levels (24-hour MBG), 24-hour standard deviation of blood glucose (24-hour SDBG), and Mean Amplitude of Glucose Excursion (MAGE) [22]. MAGE is an index of glycemic variability calculated from the value larger than one standard deviation (SD) from the mean glycemic values ± SD.…”
Section: Continuous Glucose Monitoring (Cgm) Systemmentioning
confidence: 99%
“…MAGE is an index of glycemic variability calculated from the value larger than one standard deviation (SD) from the mean glycemic values ± SD. The other indexes of glycemic variability were calculated as follows; coefficient of variance (%CV) = SD/MBG×100, and J-index =0.001 ×(MBG+SD) 2 [22].…”
Section: Continuous Glucose Monitoring (Cgm) Systemmentioning
confidence: 99%